Righteousness and identity formation in the Sermon on the Mount - Viljoen, Francois P. (HTS teologiese studies, 2013)
Righteousness is an important term in the first gospel and has a significant concentration in the Sermon on the Mount. The argument in this article is that the first gospel has a community building function. Matthew intentionally uses the word ‘righteousness’ in the Sermon on the Mount as an instrument to define the identity of his community. Though righteousness can be used in a soteriological sense, it is argued that Matthew mainly uses it in an ethical sense. By righteousness Matthew refers to the proper behavioural norms and attitudes for his community. Commitment to Jesus forms the central focus of the community’s identity. Their discipleship is demonstrated by doing the will of God as defined and interpreted by Jesus. Doing the will of God in such a manner is what Matthew regards as the distinguishing mark of this community. Thus they would surpass the righteousness of the scribes and Pharisees.